Clinical Phenotypes and Risk Predictors of Multidrug-Resistant Klebsiella Infection in a Level 3 ICU in Nepal: A Retrospective Analysis - Khanal, Kishor; Ghimire, Anup; Shrestha, Bisesh; Poudel, Saroj; Bhusal, Suraj; Pradhan, Kripa; Shrestha, Indra Kumar; Adhikari, Rakshya; Shrestha, Sanjeet Krishna; Neopane, Arpana (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Multidrug-resistant (MDR) Klebsiella infections in ICU patients are associated with increased morbidity, mortality, and prolonged ICU stay. Identifying predictors can guide empiric therapy and infection control.METHODS We conducted a retrospective review of 88 ICU patients with culture- confirmed Klebsiella over two years at Nepal Mediciti Hospital. Data collected included demographics, comorbidities, severity (APACHE II), ICU procedures, antibiotic exposure, and outcomes. Univariate and multivariable logistic regression analyses were performed to identify predictors of MDR infection.RESULTS MDR Klebsiella was identified in 65 patients (73.9%). Independent predictors included higher APACHE II score (OR 1.15; 95% CI 1.02–1.30; p = 0.022), prior antibiotic exposure (OR 4.31; 95% CI 1.34–13.9; p = 0.015), and central venous catheter (OR 3.48; 95% CI 1.05–11.5; p = 0.041). MDR patients had longer ICU stays (14.3 ± 5.8 days vs 9.7 ± 4.1 days).CONCLUSIONSSeverity of illness, prior antibiotic exposure, and invasive devices are predictors of MDR Klebsiella in ICU patients. Implementation of targeted infection control measures and antimicrobial stewardship programs can effectively reduce the MDR infection burden